Charge transfer in physics, chemistry and biology : physical mechanisms of elementary processes and an introduction to the theory /: physical mechanisms of elementary processes and an introduction to the theory. (2020) - dokt. fiz.-mat. nauk, Kuznet︠s︡ov, A. M
No abstract available